PENERAPAN MODEL PBL BERBASIS ETNOSAINS DALAM MENINGKATKAN MINAT BELAJAR IPAS SISWA KELAS V SDK WOLOWIO - Lulu, Maria Julita; Dhiu, Maria Isabela; Lawe, Yosefina Uge; Koe, Magdalena (Jurnal Ilmiah Mandalika Education (MADU), 2024)
The application of learning models that are less effective can cause a decrease in students' interest in learning, especially in science and science learning in elementary schools. This lack of interest is often caused by students' failure to solve problems related to the subject matter. This research aims to ask whether the ethnoscience-based Problem Based Learning (PBL) model can increase students' interest in learning in elementary schools. The research population consisted of 18 fifth grade students at SDK Wolowio, and the type of research used was classroom action research. Data was collected through questionnaires and tests, with the results of data analysis using qualitative descriptive. The research results showed that in cycle I, students' interest in learning in the low category reached 17%, medium 61%, and high 0%. However, in cycle II, the low category decreased to 0%, medium to 11%, and high to 89%. Based on these findings, it can be concluded that the application of the ethnoscience-based PBL model is effective in increasing students' interest in learning.